Transmembrane Helices 2 and 3 Determine the Localization of Plasma Membrane Intrinsic Proteins in Eukaryotic Cells - Wang, Hao; Zhang, Liyuan; Tao, Yuan; Wang, Zuodong; Shen, Dan; Dong, Hansong (Frontiers in Plant Science, 2020)
In plants, plasma membrane intrinsic protein (PIP) PIP1s and PIP2s mediate the transport of disparate substrates across plasma membranes (PMs), with a prerequisite that the proteins correctly localize to the PMs. While PIP2s can take correct localization by themselves in plant cells, PIP1s cannot unless aided by a specific PIP2. Here, we analyzed the localization of the Arabidopsis aquaporins, AtPIP1s, AtPIP2;4, and their mutants in yeast, Xenopus oocytes, and protoplasts of Arabidopsis. Most of AtPIP2;4 localized in the PM when expressed alone, whereas AtPIP1;1 failed to realize it in yeast and Xenopus oocytes. Switch of the transmembrane helix 2 (TM2) or TM3 from AtPIP1;1 to AtPIP2;4 disabled the latter’s PM targeting activity. Surprisingly, a replacement of TM2 and TM3 of AtPIP1;1 with those of AtPIP2;4 created a PM-localized AtPIP1;1 mutant, 1;1Δ(TM2+TM3)/2;4(TM2+TM3), which could act as a water and hydrogen peroxide channel just like AtPIP2;4. A localization and function analysis on mutants of AtPIP1;2, AtPIP1;3, AtPIP1;4, and AtPIP1;5, with the same replaced TM2 and TM3 from AtPIP2;4, showed that these AtPIP1 variants could also localize in the PM spontaneously, thus playing an inherent role in transporting solutes. Sequential and structural analysis suggested that a hydrophilic residue and a defective LxxxA motif are modulators of PM localization of AtPIP1s. These results indicate that TM2 and TM3 are necessary and, more importantly, sufficient in AtPIP2 for its PM localization.